MANAJEMEN KEGIATAN EKSTRAKULIKULER SEBAGAI PEMBENTUKAN KARAKTER SISWA LULUSAN DI MA NURUL HUDA PELEYAN KAPONGAN SITUBONDO - Hartono, Mirin (At-Turost : Journal of Islamic Studies, 2023)
The form of implementation of the teaching and learning process includes intracurricular activities and extracurricular activities. Intracurricular activities are face-to-face learning activities in the allocations that have been arranged in the structure and content of the curriculum. One of the benefits is that it can improve the character, achievement, and learning of students at school. This research is a qualitative research with data collection methods through observation, interviews and documentation which is then also supported by secondary data taken from texts which are of course related to the theme of this research. Finally, this study resulted in the conclusion that religious extracurricular activities at MA Nurul Huda Management in extracurricular activities as the formation of the character of graduate students at MA Nurul Huda Peleyan Kapongan Situbondo have fulfilled their duties, namely, how can the head of an institution or madrasah have a plan, namely the performance of teachers and accompanying teachers or Institutional monitoring of graduate students under the control of the teacher or accompanying teacher involving the outside community so that it is really managed (managed) properly, how is the coordination of the Institution with the community that will be targeted in accordance with the agreed design or plan